Reforming the Bureaucratic Frontiers: An Analysis of Legal Implications, Concepts and Challenges for Non-Civil Servant Employees in Indonesia - Ramli, Verawati; Anwary, Ichsan; Suprapto, Suprapto; Erlina, Erlina (CV. Strata Persada Academia, 2025)
The regulation of non-civil servant government employees (non-ASN) in Indonesia presents complex legal and administrative challenges amid ongoing bureaucratic reforms. The enactment of Law No. 20 of 2023 on State Civil Apparatus fundamentally redefines the status of non-ASN personnel by limiting the state apparatus to civil servants (PNS) and government employees with work agreements (PPPK), thereby mandating the transition of 2.42 million non-ASN employees into a formalized legal framework. This study employs normative legal research through statute, case, historical, comparative, and conceptual approaches to examine the legal implications of non-ASN management and to formulate a conceptual model for structuring their employment. Findings reveal that while the law introduces transformative elements such as merit-based recruitment, competence development, and digitalization, regulatory inconsistencies remain between statutory provisions and practical implementation. The research highlights the urgency of ensuring fairness, legal certainty, and transparent mechanisms to safeguard the rights of long-serving non-ASN employees. It concludes that sustainable bureaucratic reform requires a meritocratic system, inclusive governance, and continuous adaptation aligned with ethical values and technological advancements, thereby fostering professional and accountable public services.